What are the important morbidities associated with paediatric cardiac surgery? A mixed methods study. Issue 9 (9th September 2019) - Brown, Katherine L; Pagel, Christina; Ridout, Deborah; Wray, Jo; Anderson, David; Barron, David J; Cassidy, Jane; Davis, Peter; Hudson, Emma; Jones, Alison; Mclean, Andrew; Morris, Stephen; et al.
Abstract : Objectives: Given the current excellent early mortality rates for paediatric cardiac surgery, stakeholders believe that this important safety outcome should be supplemented by a wider range of measures. Our objectives were to prospectively measure the incidence of morbidities following paediatric cardiac surgery and to evaluate their clinical and health-economic impact over 6 months. Design: The design was a prospective, multicentre, multidisciplinary mixed methods study. Setting: The setting was 5 of the 10 paediatric cardiac surgery centres in the UK with 21 months recruitment. Participants: Included were 3090 paediatric cardiac surgeries, of which 666 patients were recruited to an impact substudy. Results: Families and clinicians prioritised: Acute neurological event, unplanned re-intervention, feeding problems, renal replacement therapy, major adverse events, extracorporeal life support, necrotising enterocolitis, postsurgical infection and prolonged pleural effusion or chylothorax. Among 3090 consecutive surgeries, there were 675 (21.8%) with at least one of these morbidities. Independent risk factors for morbidity included neonatal age, complex heart disease and prolonged cardiopulmonary bypass (p<0.001). Among patients with morbidity, 6-month survival was 88.2% (95% CI 85.4 to 90.6) compared with 99.3% (95% CI 98.9 to 99.6) with none of the morbidities (p<0.001). The impact substudy in 340 children with morbidity and 326 control children with no morbidity indicated that morbidity-related impairment in quality of life improved between 6 weeks and 6 months. When compared with children with no morbidities, those with morbidity experienced a median of 13 (95% CI 10.2 to 15.8, p<0.001) fewer days at home by 6 months, and an adjusted incremental cost of £21 292 (95% CI £17 694 to £32 423, p<0.001). Conclusions: Evaluation of postoperative morbidity is more complicated than measuring early mortality. However, tracking morbidity after paediatric cardiac surgery over 6 months offers stakeholders important data that are of value to parents and will be useful in driving future quality improvement.